1983
DOI: 10.1161/01.cir.68.1.88
|View full text |Cite
|
Sign up to set email alerts
|

Amiodarone: clinical efficacy and toxicity in 96 patients with recurrent, drug-refractory arrhythmias.

Abstract: Ninety-six patients with recurrent, drug-refractory tachyarrhythmias were treated with amiodarone for 8.0 + 7.5 months (range 1 day to 27 months): 77 for recurrent ventricular tachycardia or ventricular fibrillation (VT/VF), two for complex ventricular ectopy, and 17 for supraventricular tachyarrhythmias. The actuarial incidence of successful amiodarone therapy was 52 + 7% at 12 months and 28 + 9% at 24 months for patients with VT/VF. Neither patient with complex ventricular ectopy was successfully treated. Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
1
5

Year Published

1983
1983
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(55 citation statements)
references
References 24 publications
0
49
1
5
Order By: Relevance
“…86,88 The incidence of this complication appears to be low (Ͻ0.5%). Many large follow-up studies have reported no cases, 8,29,31 including the 2 largest (with 462 and 589 patients, respectively). 35,36 Use of programmed electrical stimulation can define a different type of potential proarrhythmic effect of antiarrhythmic drugs.…”
Section: Cardiac Safety Of Amiodaronementioning
confidence: 99%
See 1 more Smart Citation
“…86,88 The incidence of this complication appears to be low (Ͻ0.5%). Many large follow-up studies have reported no cases, 8,29,31 including the 2 largest (with 462 and 589 patients, respectively). 35,36 Use of programmed electrical stimulation can define a different type of potential proarrhythmic effect of antiarrhythmic drugs.…”
Section: Cardiac Safety Of Amiodaronementioning
confidence: 99%
“…Virtually all available publications merely report the outcomes of patients with resuscitated cardiac arrest or recurrent VT treated with amiodarone. [25][26][27][28][29][30][31][32][33][34][35] Most reports conclude that amiodarone is an effective agent, 8,[25][26][27][28][29] although some suggest that amiodarone is not as effective as claimed by early enthusiastic reports. 34 It is not possible to draw any firm conclusions about the efficacy of amiodarone from these uncontrolled reports.…”
Section: Ventricular Tachyarrhythmiasmentioning
confidence: 99%
“…Embora seja um anti-arrítmico efetivo, provoca diversos efeitos colaterais em 60 a 93% dos indivíduos que fazem uso da droga, tais como depósitos corneanos secundários à pigmentação do epitélio, alterações tireoidianas e hepáticas, insuficiência cardíaca, bradicardia, neurotoxicidade e fibrose pulmonar (2)(3)(4)(5)(6) . Desses, o mais sério é a toxicidade pulmonar, caracterizada por pneumonite intersticial -que ocorre em 5 a 7% dos indivíduos tratados com amiodarona -e que, em geral, evolui para fibrose pulmonar (5)(6)(7)(8)(9) . Acomete predominantemente indivíduos do sexo masculino com mais de 50 anos (5,8) e sua mortalidade está estimada em torno de 5 a 10% dos casos (2,6) .…”
Section: Introductionunclassified
“…Desses, o mais sério é a toxicidade pulmonar, caracterizada por pneumonite intersticial -que ocorre em 5 a 7% dos indivíduos tratados com amiodarona -e que, em geral, evolui para fibrose pulmonar (5)(6)(7)(8)(9) . Acomete predominantemente indivíduos do sexo masculino com mais de 50 anos (5,8) e sua mortalidade está estimada em torno de 5 a 10% dos casos (2,6) .…”
Section: Introductionunclassified
“…Serial electrophysiologic testing has improved the ability to select an effective drug, but has also exposed the inadequacies of currently available antiarrhythmic agents. A drug likely to prevent arrhythmia recurrence can be identified in less than 35% of patients with recurrent VTA (Spielman et al, 1983;Swerdlow et al, 1983). Furthermore, a substantial number of patients develop intolerable adverse reactions or worsening of arrhythmias with medical therapy (Fogoros et al, 1983;Velebit et al, 1982).…”
Section: Introductionmentioning
confidence: 99%